2013
DOI: 10.1371/journal.pone.0059897
|View full text |Cite
|
Sign up to set email alerts
|

The Gating Mechanism of the Human Aquaporin 5 Revealed by Molecular Dynamics Simulations

Abstract: Aquaporins are protein channels located across the cell membrane with the role of conducting water or other small sugar alcohol molecules (aquaglyceroporins). The high-resolution X-ray structure of the human aquaporin 5 (HsAQP5) shows that HsAQP5, as all the other known aquaporins, exhibits tetrameric structure. By means of molecular dynamics simulations we analyzed the role of spontaneous fluctuations on the structural behavior of the human AQP5. We found that different conformations within the tetramer lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 69 publications
4
65
0
Order By: Relevance
“…A gating mechanism regulating human AQP5 activity has been proposed by molecular dynamics simulations [33]. This study revealed that the AQP5 channel could change between an open and closed state by a tap-like mechanism at the cytoplasmic end, induced by a translation of the His67 inside the pore, blocking the entrance of the channel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A gating mechanism regulating human AQP5 activity has been proposed by molecular dynamics simulations [33]. This study revealed that the AQP5 channel could change between an open and closed state by a tap-like mechanism at the cytoplasmic end, induced by a translation of the His67 inside the pore, blocking the entrance of the channel.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 3B the top view of the monomer is depicted, with His173 and Ser183 located in the selectivity filter (SF). The distance between these two residues (8.4 Å) was proposed to correspond to the pore wide conformation [33]. All these residues are conserved in rat AQP5 sequence (Figure S1) with the exception of Ser233.…”
Section: Resultsmentioning
confidence: 99%
“…Recent molecular dynamics simulations have suggested that a novel gating mechanism operates in AQP5, in which monomeric channels are in distinct open or closed conformations 16 . This finding adds to the knowledge of the structural basis of AQP gating 17 ; previous experimentally and computationally derived mechanisms proposed that AQP gating involved mechanosensitivity and phosphorylation in yeast AQPs 18 , and membrane tension in both mammalian and yeast AQPs 1921 .…”
Section: Aqp Structure and Functionmentioning
confidence: 99%
“…The longer simulation time allowed us to identify the reorientation of the side chain of T62 as a key element for epitope recognition and thus for NMO-IgG binding. In recent years molecular dynamics (MD) simulations proved effective to obtain important structural and mechanistic insights into the water transport of aquaporins [26][27][28][29][30][31][32][33]. Here, we employ the same technique to obtain some insight on NMO-IgG epitope reorganization.…”
Section: Introductionmentioning
confidence: 99%